THE INTEGRATED LEARNING MODEL TYPE OF “CONNECTED” IN INCREASING THE STUDENTS’ LEARNING CREATIVITY AND ABILITY - Diani Syahputri Syahputri; Elfrianto Elfrianto Elfrianto (State Islamic University of North Sumatra Indonesia, 2018)
This study aims to: 1) Analyze the application of integrated learning model of type connected in reminding creativity and students' learning ability; 2) Analyze student response after application of connected learning model; 3) Evaluate students' creativity and learning ability after applied learning model. This research was conducted at University of Muhammadiyah Sumatera Utara. The study was conducted in two years. The first year starts from November 2016 to July 2017 and continues the second year beginning in September 2017 until May 2018. Data are collected from observations and questionnaires. Data analysis is done by finding mean, mastery, ability and creativity of students. The results showed that integrated learning method type connected can increase creativity, generate positive responses to learning and improve student learning ability